The role of slametan in the discourse on Javanese Islam. Issue 133 (2nd September 2017) - van den Boogert, Jochem
ABSTRACT: This article examines different dominant scholarly representations of the Javanese slametan ritual, with a special focus on its representation as a syncretist ritual. Such syncretism is often seen as the source of Java's social harmony and religious tolerance. My analysis shows that these representations are identically structured as expressions of beliefs. However, this seems not to be corroborated by Javanese reflections on the slametan . An analysis of the 19th-century origins of the discourse on Javanese Islam shows that both this religion and the role of the slametan in it were conceived within a Christian theological framework. Furthermore, the logical consistency of that original depiction depends on two main assumptions, which today can no longer be assumed. Considering the well documented, steady demise of the syncretist slametan, and perhaps also of the concomitant religious tolerance, there is an urgent need to develop a new scholarly understanding of this Javanese tradition. Positioned at a meta-level, this article does not discuss slametan, syncretism, and Javanese Islam as such, but rather critically assesses the study of it.